THE EFFECT OF MOTIVATION, WORK ENVIRONMENT, AND JOB SATISFACTION ON IMPROVING TEACHER PERFORMANCE IN CLUSTER 02 SENIOR HIGH SCHOOL IN TANGERANG REGENCY - Muhamad Badru Ulum; Misdiono Misdiono (Dinasti International Journal of Education Management And Social Science, 2022)
The main problem in this research is some teachers do not show maximum performance. Many factors can influence teacher performance, but in this study analyzed through motivation, work environment and job satisfactionThe purpose of this study was to determine the effect of work Motivation, work environment, and job satisfaction on improving the performance of high school teachers in Cluster 02 Kab. Tangerang. The approach of this take a look at quantitative technique and the use of assorted quantitative correlation. The collecting data using four types of questionaire about motivation, work environment, job satisfaction, and work performance. The number of respondent in this study is 65 teacher. The data were analyzed using descriptive statistics and multiple linear regression analysis. The results of the study showed that, There is a positive and insignificant influence on the motivation toward teacher performance, this is explained by the significant value of data that t count 1.184 < t table 1.998 and the significant of t test that 0.241 > 0.05. There is a positive and insignificant influence on the work environment toward teacher performance, this is explained by the significant value of data that t count -0.012 < t table 1.998 and the significant of t test that 0.991 > 0.05. There is a positive and significant influence on the job satisfaction toward teacher performance, this is explained by the significant value of data that t count 3.502 > t table 1.998 and the significant of t test that 0.001 < 0.05. there are simultaneous of positive and significant influence from motivation, work environment, and job satisfaction toward teachers. It based on the F significant value of 0.000 < 0.05. the value of R square is equal to 0.471, so that 47.1% and the remaining 52.9% influenced by other variabels.